Why are banks not recapitalized during crises? - Matteo Crosignani (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
I develop a model where the sovereign debt capacity depends on the capitalization of domestic banks. Low-capital banks optimally tilt their government bond portfolio toward domestic securities, linking their destiny to that of the sovereign. If the sovereign risk is sufficiently high, low-capital banks reduce private lending to further increase their holdings of domestic government bonds, lowering sovereign yields and supporting the home sovereign debt capacity. The model rationalizes, in the context of the eurozone periphery, the increase in domestic government bond holdings, the reduction of bank credit supply, and the prolonged fragility of the financial sector.
Keywords: E44; F33; G21; G28; 330; Bank Capital; Sovereign Crises; Risk-Shifting; Government Bonds; Bank Credit